Developing of Authentic Assessment Model Learning to Appreciate Drama Texts: A Pilot Test with Senior High School Students - Nurizzati Nurizzati; Ermawati Arief; Ena Noveria (AL-ISHLAH: Jurnal Pendidikan, 2023)
This research is motivated by a lack of teacher attention in managing literary appreciation learning with evidence of the lack of completeness of the assessment tools in the teacher's lesson plans. Therefore, the purpose of this study was to develop an authentic assessment model to measure the achievement of basic competence (KD) in learning the ability to appreciate literary texts (drama) for the class XI 2013 curriculum at the SMA/MA/SMK level, which focused on psychomotor and affective domains which were the focus of learning achievement on literary appreciation by first perform needs analysis, KD analysis, material analysis, and student analysis. To achieve the objectives of this study, the theory of assessment and authentic assessment was used; learning theory and development of learning device models; literary and educational theory; and learning theory of the ability to appreciate literary texts. The design implications for the development of this model refer to the 4-D model suggested by Thiagarajan, Semel and Semel (1974) which consists of 4 stages, namely define, design, develop and disseminate. The type of research is R D development research. The data of this research consists of two groups, namely qualitative data in the form of assessment model development tools, and quantitative data in the form of achievement scores of performance tasks with authentic instruments whose limited trials and dissemination were carried out in Senior High School in Padang city. The result of the research is an assessment model that is based on social cognitive learning theory, constructivism, and meaningful learning, learning syntax that focuses on students with representative assessment tools. The results of testing the assessment tool which consisted of 10 types of instruments were concluded to be able to measure the level and type of appreciation of students' literature with a "Good" qualification.